2020
DOI: 10.1093/beheco/araa092
|View full text |Cite
|
Sign up to set email alerts
|

An experimental test to separate the effects of male age and mating history on female mate choice

Abstract: Should females prefer older males as mates? Male survival to old age might indicate the presence of fitness-enhancing genes that increase offspring fitness. However, many correlational studies show that mating with older males can lower female fecundity and even reduce offspring fitness due to epigenetic or germline mutation effects. One problem in quantifying female choice based on male age is that age is usually confounded with mating history. This begs a question: Do females choose males based on their age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 69 publications
0
23
0
Order By: Relevance
“…Because female mating status does not influence her mate choice in G. holbrooki (Aich et al. 2020), we defined male attractiveness as the proportion of the total trial time the female spent within each association zone.…”
Section: Methodsmentioning
confidence: 99%
“…Because female mating status does not influence her mate choice in G. holbrooki (Aich et al. 2020), we defined male attractiveness as the proportion of the total trial time the female spent within each association zone.…”
Section: Methodsmentioning
confidence: 99%
“…To examine the effects of male age and mating history on sperm traits and reproductive success, we bred 'young' and 'old' males in the laboratory and then assigned males in each age class to one of two mating treatments (full methodological details in [33]). In brief, 'old' and 'young' males were bred from laboratory stocks in batches 12 weeks apart.…”
Section: (B) Manipulating Male Age and Mating Historymentioning
confidence: 99%
“…Intriguingly, we found that rearing temperature altered the phenotypic correlation between body size and sperm velocity: when reared at the warmer temperature larger males had faster‐swimming sperm, but the reverse was the case for males reared at the cooler temperatures. Larger male mosquito fish are generally more attractive to females (Aich et al., 2020; Bisazza et al., 2001; Kahn et al., 2010) and have greater insemination success per mating attempt (Head et al., 2015). However, precopulatory sexual selection on male size in mosquito fish is complex and there is also evidence that smaller males are better at sneaking copulations with females (Pilastro et al., 1997) and, as a consequence, sometimes have greater reproductive success than larger males (Head et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable research looking at targets of precopulatory sexual selection in G. holbrooki . Several studies report that females prefer to associate with larger males (Aich et al., 2020; Bisazza & Marin, 1991; Hughes, 1985) which implies a large male mating advantage. On the other hand, some studies report that smaller males have a greater insemination success per mating attempt (Pilastro et al., 1997), whereas others find that larger males are more effective (Booksmythe et al., 2013).…”
Section: Introductionmentioning
confidence: 99%